A large-scale screening for the taiga tick, Ixodes persulcatus, and the meadow tick, Dermacentor reticulatus, in southern Scandinavia, 2016 - Lene Jung Kjær; Arnulf Soleng; Kristin Skarsfjord Edgar; Heidi Elisabeth H. Lindstedt; Katrine Mørk Paulsen; Åshild Kristine Andreassen; Lars Korslund; Vivian Kjelland; Audun Slettan; Snorre Stuen; Petter Kjellander; Madeleine Christensson; et al. (Parasites & Vectors, 2019)
Abstract The taiga tick, Ixodes persulcatus, has previously been limited to eastern Europe and northern Asia, but recently its range has expanded to Finland and northern Sweden. The species is of medical importance, as it, along with a string of other pathogens, may carry the Siberian and Far Eastern subtypes of tick-borne encephalitis virus. These subtypes appear to cause more severe disease, with higher fatality rates than the central European subtype. Until recently, the meadow tick, Dermacentor reticulatus, has been absent from Scandinavia, but has now been detected in Denmark, Norway and Sweden. Dermacentor reticulatus carries, along with other pathogens, Babesia canis and Rickettsia raoultii. Babesia canis causes severe and often fatal canine babesiosis, and R. raoultii may cause disease in humans. We collected 600 tick nymphs from each of 50 randomly selected sites in Denmark, southern Norway and south-eastern Sweden in August–September 2016. We tested pools of 10 nymphs in a Fluidigm real time PCR chip to screen for I. persulcatus and D. reticulatus, as well as tick-borne pathogens. Of all the 30,000 nymphs tested, none were I. persulcatus or D. reticulatus. Our results suggest that I. persulcatus is still limited to the northern parts of Sweden, and have not expanded into southern parts of Scandinavia. According to literature reports and supported by our screening results, D. reticulatus may yet only be an occasional guest in Scandinavia without established populations.